Role of mordenite zeolite in improving nutrient and water use efficiency in Alfisols - V, Girijaveni; K, Sammi Reddy; Ch, Srinivasarao; B M K, Raju; Balakrishnan, Divya; Kundu, Sumanta; Pushpanjali; Rohit, Jagriti; V K, Singh; Pushpanjali (Frontiers in Plant Science, 2025)
zeolites are naturally available minerals with very high cation exchange and water holding capacity that can improve nutrient use efficiency (NUE) and water use efficiency (WUE) in crop production. Moreover, zeolites are safe for the environment and living organisms, and their use in agriculture results in improving physical and chemical properties of soil. Yet, its application is very limited in semi-arid regions of India. Thus, a study was conducted with locally available zeolite at CRIDA, Hyderabad, was further characterized using XRD and SEM, as the type zeolite collected is unknown.. The results of XRD and SEM revealed that the zeolite collected was mordenite zeolite. Further, sorption and leaching column study were carried to evaluate the zeolite capacity to hold and release the nutrients especially NH4 + , P and K and found that the maximum adsorption capacity for NH 4 + , P and K were estimated as 10.6, 1.08 and 2.15 mg g -1 respectively suggesting the zeolite has good affinity for N. Further, column study revealed that there was 15.4% reduction in NH 4 + -N loss with 10 t zeolite ha -1 + N @100 kg ha -1 as compared to N alone while the reduction was 39.6% with 10 t zeolite ha -1 + N @500 kg ha -1 compared to N alone suggesting that the zeolite could control the release of N as compared to sole application of N. Further, pot experiment was carried out with three levels of fertilizer rates, four levels of zeolite and two levels of moisture in randomised complete block design with three replications with tomato as test crop. There was significant positive impact on yield, water use efficiency, nutrient (N, P and K) uptake and soil available nutrients. Highest soil available N, P and K, crop uptake and yield was observed due to zeolite application @ 200 kg ha -1 along with 100% recommended dose of fertilization in Alfisols. Thus, zeolite application along with chemical fertilizers can improve the nutrient availability by reducing the leaching losses and improving nutrient use efficiency.